Conformal graphene directly synthesized on intracavity whispering gallery mode microresonators for GHz repetition rate mode-locked lasers - Kovalchuk, Oleksiy; Lee, Sungjae; Moon, Hyowon; Armani, Andrea M.; Song, Yong-Won (2024 IEEE PHOTONICS CONFERENCE, IPC 2024, 2024)
We demonstrate tunable GHz-pulse fiber lasers by combining spectral filtering with conformal graphene. A microresonator filters modes, and graphene induces mode-locking, enabling pulses exceeding 150 GHz with up to 6.1 GHz tunability through graphene's photo-thermal effect.